The Diversity of Sphingidae (Insecta: Lepidoptera) in Koritniku Mountain, The Republic of Kosova - Bytyçi, Pajtim; Zhushi-Etemi, Ferdije; Kabashi-Kastrati, Edona; Koren, Toni (Polish Journal of Natural Sciences, 2023)
Moths of the family Sphingidae are large and usually easily recognizable moths, that remain not sufficiently surveyed in some parts of Europe, including the Republic of Kosovo. From 2020 to 2022, Sphingidae diversity was surveyed in Kosovo’s part of mountain Koritniku, near the border with Albania. The moths were collected with light traps in the period April-October in each year of the survey. In total 12 Sphingidae species were recorded, which compose about 27.5% of European fauna. Of those, 8 have been recorded in Kosovo for the first time: Daphnis nerii (Linnaeus, 1758), Deilephila elpenor (Linnaeus, 1758), Hyles livornica (Esper, 1780), Acherontia atropos (Linnaeus, 1758), Marumba quercus (Denis & Schiffermüller, 1775), Laothoe populi (Linnaeus, 1758), Mimas tiliae (Linnaeus, 1758), Smerinthus ocellata (Linnaeus, 1758). The recorded number of Sphingidae species in our research is only a modest contribution to a better knowledge of the moth fauna of Kosovo, but still represents an update in comparison with historical records. Considering the number of species of this family in neighboring countries, we can suppose that the number of recorded species is not a final one and further research is needed.